2015
DOI: 10.1002/glia.22837
|View full text |Cite
|
Sign up to set email alerts
|

Striatal astrocytes transdifferentiate into functional mature neurons following ischemic brain injury

Abstract: To determine whether reactive astrocytes stimulated by brain injury can transdifferentiate into functional new neurons, we labeled these cells by injecting a glial fibrillary acidic protein (GFAP) targeted enhanced green fluorescence protein plasmid (pGfa2‐eGFP plasmid) into the striatum of adult rats immediately following a transient middle cerebral artery occlusion (MCAO) and performed immunolabeling with specific neuronal markers to trace the neural fates of eGFP‐expressing (GFP+) reactive astrocytes. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
89
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 86 publications
(95 citation statements)
references
References 35 publications
(52 reference statements)
2
89
0
Order By: Relevance
“…They modulate the myelinating capacity of the oligodendrocytes 4 , the synaptic cross-talk amongst neurons 5 , the homeostasis of the CNS extracellular medium 6 , the initiation of the inflammatory and immune responses 7 and the building up of barriers between normal and damaged tissues 8 . Astrocytes can behave like phagocytic cells 9 , they sense the partial pressure of O 2 within the CNS 10 and they can transform into neurons when the brain is in need of rebuilding damaged functional neural networks contributing to nervous tissue repair 11 . Therefore, we believe that the astrocyte deserves to be considered, in its own right, one of the main players orchestrating fundamental functions within the CNS.…”
Section: Astrocytes In Physiologymentioning
confidence: 99%
“…They modulate the myelinating capacity of the oligodendrocytes 4 , the synaptic cross-talk amongst neurons 5 , the homeostasis of the CNS extracellular medium 6 , the initiation of the inflammatory and immune responses 7 and the building up of barriers between normal and damaged tissues 8 . Astrocytes can behave like phagocytic cells 9 , they sense the partial pressure of O 2 within the CNS 10 and they can transform into neurons when the brain is in need of rebuilding damaged functional neural networks contributing to nervous tissue repair 11 . Therefore, we believe that the astrocyte deserves to be considered, in its own right, one of the main players orchestrating fundamental functions within the CNS.…”
Section: Astrocytes In Physiologymentioning
confidence: 99%
“…But we and others have recently found that parenchymal astrocytes residing in the striatum can also generate neurons (Magnusson et al, 2014;Nato et al, 2015;Luzzati et al, 2014;Duan et al, 2015;Shen et al, 2015). These striatal astrocytes are triggered by certain injuries, such as stroke, to activate latent neurogenic properties and produce neurons in a burst of proliferation (Fig.…”
Section: Striatummentioning
confidence: 95%
“…3). As mentioned, the similarities between parenchymal astrocytes and neural stem cells even extend to an intrinsic capacity of parenchymal astrocytes to generate neurons, at least when it comes to striatal astrocytes in vivo (Magnusson et al, 2014;Nato et al, 2015;Duan et al, 2015;Luzzati et al, 2014) and cortical astrocytes when isolated and cultured in vitro (Buffo et al, 2008;Shimada et al, 2012;Sirko et al, 2013). But the relatedness between the two cell types might go even further than that.…”
Section: Regional Differences In the Astrocyte Phenotypementioning
confidence: 99%
“…In favor of this argument, glial cells in multiple contexts have been shown to maintain mitotic activity (Doetsch 2003). This capacity may reveal itself immediately by the amplification of the glial population, or later upon activation in adulthood (Guo, Zhang et al 2014, Duan, Liu et al 2015, Sammut, Cook et al 2015). This difference in proliferative capacity may be mediated by the different levels of Prospero inherited by the terminally dividing neuroblast to its progeny.…”
Section: Emerging Ideasmentioning
confidence: 99%